2020
DOI: 10.1155/2020/2190494
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Performance in a Selected Sample of Dairy Farms in Una-Sana Canton, Bosnia and Herzegovina

Abstract: Background. e production of milk and dairy products and their placement on the market represent a constant profit for the farmers/producers in Bosnia and Herzegovina (BH). e profitable operation of the dairy farms is influenced by the reproductive performance of the lactating animals. is study assessed individual animal reproductive characteristics in selected dairy farms and described their reproductive performance indicators. Results. e median age at first insemination was 493 days (5 th -95 th percentile ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Those variations might be due to different genetic architectures, the environment, herd management and practices, and disease. Similarly, Softic et al [37] also reported that extended CFI was influenced by several factors such as nutrition, endometritis, and a lack of estrus detection. The other factor, uterine infection, has been associated with extended CFI in dairy cattle and low reproductive performance [33,38].…”
Section: Calving To First Service Interval (Cfi)mentioning
confidence: 91%
“…Those variations might be due to different genetic architectures, the environment, herd management and practices, and disease. Similarly, Softic et al [37] also reported that extended CFI was influenced by several factors such as nutrition, endometritis, and a lack of estrus detection. The other factor, uterine infection, has been associated with extended CFI in dairy cattle and low reproductive performance [33,38].…”
Section: Calving To First Service Interval (Cfi)mentioning
confidence: 91%
“…The calculation of the reproduction traits is described below. Post-Partum Mating (PPM) was calculated by subtracting the first service after the parturition date from parturition date (day) as described [10]. The PPM formula is described in the formula (1).…”
Section: Genotypingmentioning
confidence: 99%
“…Calving Interval (CI) was measured by subtracting the calving date from the date of calving before and recorded in day, as described by [10]. The CI formula is expressed in the formula (3), where n is the calving number.…”
Section: Sc = ∑ S (2)mentioning
confidence: 99%
“…The reproductive performance of modern dairy cows globally has decreased over the past 50 years (Softic et al 2020). This scenario is further exacerbated due to the emphasis on the selection and rearing of animals for specific commercial purposes, which compromises livestock reproduction (Yoo 2010).…”
Section: Introductionmentioning
confidence: 99%